Hybrid Pedagogy and Digital Literacy in Islamic Religious Education at an Open University - Lukis Alam; Muhammad Sulaiman; Fathiya Azka Awliya (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2026)
The purpose of this research was to analyze the implementation of hybrid pedagogy and its impact on students’ digital literacy in Islamic Religious Education at Universitas Terbuka Indonesia. A qualitative field work design was used for data collection, through interviews, LMS observation and document analysis. The results demonstrate that hybrid pedagogy allows flexible learning with asynchronous resources and synchronous interaction. However, the students’ variation in digital literacy affects their participation in synchronous classes and digital assignments for digital discussions. The study also finds issues such as the digital divide, limited access to digital devices, platform usability, large class sizes, and unequal institutional support. The findings of this study indicate that hybrid Islamic religious education needs to be developed more sophisticatedly in areas of digital literacy, lecturers’ pedagogical preparedness, and inclusive institutional support to spur academic engagement, ethical reflection, and spiritual growth.